Serum Untargeted UHPLC-HRMS-Based Lipidomics to Discover the Potential Biomarker of Colorectal Advanced Adenoma - Zhu Y (Dove Medical Press, 2021)
Yifan Zhu,1,* Lisheng Wang,1,* Yanying Nong,2 Yunxiao Liang,3 Zongsheng Huang,3 Pingchuan Zhu,4 Qisong Zhang1 1Medical College of Guangxi University, Guangxi University, Nanning, Guangxi, 530004, People’s Republic of China; 2Department of Gastroenterology, Ruikang Hospital Affiliated to Guangxi University of Chinese Medicine, Nanning, Guangxi, 530011, People’s Republic of China; 3Department of Gastroenterology, The People’s Hospital of Guangxi Zhuang Autonomous Region, Nanning, Guangxi, 530021, People’s Republic of China; 4State Key Laboratory for Conservation and Utilization of Subtropical Agro-Bioresources, Guangxi University, Nanning, Guangxi, 530004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qisong ZhangMedical College of Guangxi University, Guangxi University, No. 100, East Daxue Road, Nanning, Guangxi, 530004, People’s Republic of ChinaTel +86 0771-3387105Email zhangqisong@gxu.edu.cnBackground: As a key precancerous lesion, colorectal advanced adenoma (CAA) is closely related to the occurrence and development of colorectal cancer (CRC). Effective identification of CAA-related biomarkers can prevent CRC morbidity and mortality. Lipids, as an important endogenous substance, have been proved to be involved in the occurrence and development of CRC. Lipidomics is an advanced technique that studies lipid metabolism and biomarkers of diseases. However, there are no lipidomics studies based on large serum samples to explore diagnostic biomarkers for CAA.Methods: An integrated serum lipid profile from 50 normal (NR) and 46 CAA subjects was performed using ultra-high performance liquid chromatography tandem high-resolution mass spectrometry (UHPLC-HRMS). Lipidomic data were acquired for negative and positive ionization modes, respectively. Differential lipids were selected by univariate and multivariate statistics analyses. A receiver operator characteristic curve (ROC) analysis was conducted to evaluate the diagnostic performance of differential lipids.Results: A total of 53 differential lipids were obtained by combining univariate and multivariate statistical analyses (P < 0.05 and VIP > 1). In addition, 12 differential lipids showed good diagnostic performance (AUC > 0.90) for the discrimination of NR and CAA by receiver operating characteristic curve (ROC) analysis. Of them, the performance of PC 44:5 and PC 35:6e presented the outstanding performance (AUC = 1.00, (95% CI, 1.00– 1.00)). Moreover, triglyceride (TAG) had the highest proportion (37.74%) as the major dysregulated lipids in the CAA.Conclusion: This is the first study that profiled serum lipidomics and explored lipid biomarkers with good diagnostic ability of CAA to contribute to the early prevention of CRC. Twelve differential lipids that effectively discriminate between NR and CAA serve as the potential diagnostic markers of CAA. An obvious perturbation of TAG metabolism could be involved in the CAA formation.Keywords: colorectal advanced adenoma, biomarker, serum lipidomics, UHPLC-HRMS, colorectal cancer